Study of acute encephalitis syndrome in children - Khinchi, YR; Kumar, A; Yadav, S (Journal of College of Medical Sciences-Nepal, 2010)
Objective: To determine the profile and outcome of children admitted with Acute Encephalitis Syndrome (AES) and to find out the prevalence of Japanese Encephalitis (JE) IgM antibodies positive cases among these patients with their case fatality rate (CFR). Materials and methods: Study consist of retrospective analysis of hospital records of children up to 15 years of age admitted with diagnosis of AES in pediatric wards of College of Medical Sciences-Teaching Hospital, Bharatpur from January 2007 to December 2008. Results: During two years, 61 patients of AES were admitted. Male and female patients were 33 and 28 respectively. Meningitis accounted for 29 and encephalitis for 32 patients. JE IgM seropositive cases contributed for 18% of all AES cases. Case fatality for JE was 16.6%. Conclusions: Japanese Encephalitis is endemic in catchment area of the hospital. JE has significant morbidity and mortality which can be prevented by immunization and mortality can be reduced if supportive interventions are provided in time. Key words: AES; JE; CFR. DOI: 10.3126/jcmsn.v6i1.3596 Journal of College of Medical Sciences-Nepal, 2010, Vol. 6, No. 1, 7-13